Words of common sense for mind, body, and soul - Steindl-Rast, David (Templeton Foundation Press, 2002)
Brother David Steindl-Rast takes us on a journey of discovery by identifying the wonder of the ordinary found in common sense. In a humble and insightful way he illuminates the teachings that are passed from one generation to the next. These words of common sense bring to light the important virtues and ethics that are valued by human beings worldwide. ""When you drink from a stream, remember the spring,"" says a wise Chinese proverb that evokes thanksgiving and reflection. ""A contented heart is a continual feast"" directs a person to look within for their happiness rather tha.